2003
DOI: 10.1016/s0893-6080(03)00112-6
|View full text |Cite
|
Sign up to set email alerts
|

A network for recursive extraction of canonical coordinates

Abstract: A network structure for canonical coordinate decomposition is presented. The network consists of two single-layer linear subnetworks that together extract the canonical coordinates of two data channels. The connection weights of the networks are trained by a stochastic gradient descent learning algorithm. Each subnetwork features a hierarchical set of lateral connections among its outputs. The lateral connections perform a deflation process that subtracts the contributions of the already extracted coordinates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…In efforts to reduce the complexity of the problem, only the first half of the canonical correlations are used as features in the ensuing classification problem. This is justified since only the first few canonical correlations yield the greatest contribution to the linear dependence or mutual information between the data channels [6]. Figures 3(a) and (b) show the plots of canonical correlation features obtained for mine-like and non-mine-like objects via CCA and MCCA, respectively.…”
Section: Feature Extraction and Classificationmentioning
confidence: 96%
See 4 more Smart Citations
“…In efforts to reduce the complexity of the problem, only the first half of the canonical correlations are used as features in the ensuing classification problem. This is justified since only the first few canonical correlations yield the greatest contribution to the linear dependence or mutual information between the data channels [6]. Figures 3(a) and (b) show the plots of canonical correlation features obtained for mine-like and non-mine-like objects via CCA and MCCA, respectively.…”
Section: Feature Extraction and Classificationmentioning
confidence: 96%
“…It is well-known that canonical correlation analysis (CCA) provides an elegant framework [6] for analyzing linear dependence and mutual information between two data channels. The results of [7] showed that MCCA provides a useful measure used to interpret and summarize the evolution of psoriasis in medical patients.…”
Section: Multichannel Canonical Correlation Analysismentioning
confidence: 99%
See 3 more Smart Citations